Molecular epidemiology of piliated pneumococcal isolates at a major tertiary hospital in the Klang Valley, Malaysia - Dzaraly, Nurul Diana; Mohd Desa, Mohd Nasir; Muthanna, Abdulrahman; Masri, Siti Norbaya; Mohd Taib, Niazlin; Zainal Baharin, Nurul Hana; Sulaiman, Nurshahira; Abdul Rahman, Nurul Asyikin; Palanisamy, Navindra Kumari; Suhaili, Zarizal; Yusuff, Semiat Opeyemi; Rahman, Nor Iza A.; et al. (Medknow Publications, 2023)
Objective: To characterise a collection of pili-carrying and none pili-carrying pneumococcal isolates of clinical origin for serotypes, antibiotic resistance and genotype. Methods: In total, 42 clinical isolates were collected between October 2017 and December 2019. Those isolates were analysed for antimicrobial susceptibility, serotype distribution, detection of pneumococcal virulence and pilus genes. Multilocus sequence typing was performed only for piliated isolates, followed by phylogenetic analysis. Results: The common isolation sites among the pneumococcal isolates were tracheal aspirate (28.6%), blood (26.2%), and sputum (23.8%). Fifty percent isolates were resistant to erythromycin, tetracycline (50.0%) and trimethoprim-sulfamethoxazole (43.0%). The most frequent were serotypes 19F (28.6%), 6A/B (23.8%) and 19A (14.3%). Piliated isolates were detected in a small proportion (33.3%); 64.3% were multidrug-resistant. ST320 was the prevalent sequence type among the piliated isolates and genetically related to the Pneumococcal Molecular Epidemiology Network clones Taiwan19F-14 (CC271). In the phylogenetic analysis, some piliated isolates showed a close association having similar ST320, carrying serotype 19A and both pilus genes indicating their clonal spread. Conclusions: Pneumococcal lineages of piliated isolates have been globally disseminated and pili could have played a role in the spread of antibiotic resistant clones.